2020
DOI: 10.3389/fenrg.2020.00162
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Energy Transition Patterns in Asia: Evidence From Countries With Different Income Levels

Abstract: Energy transition as the issue of striving to use more environmentally friendly energy sources instead of fossil fuels is a crucial debate for scholars. A key point is how macroeconomic variables can accelerate the energy transition movement in different regions, which may lead to similarities in energy transition patterns among various regions. The main purpose of this study is to determine how energy transition patterns depend on economic variables in Asian economies, classifying based on their income level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…This can be attributed to the spillover effect of FDI, as the economies' technical capacity gradually improves due to the inflow of foreign capital and exposure to advanced management practices. Our outcomes are consistent with Shahbaz et al [136] and Reyes et al [137] and in contrast with the findings of several earlier studies [138][139][140].…”
Section: Long-run Results Of Amg (Panel)supporting
confidence: 92%
“…This can be attributed to the spillover effect of FDI, as the economies' technical capacity gradually improves due to the inflow of foreign capital and exposure to advanced management practices. Our outcomes are consistent with Shahbaz et al [136] and Reyes et al [137] and in contrast with the findings of several earlier studies [138][139][140].…”
Section: Long-run Results Of Amg (Panel)supporting
confidence: 92%
“…It could be attained through energy efficiency, energy pricing, energy intensity, technological innovation, or building high-tech industries. The authors of [22] investigated the role of efficiency growth and convergence to enhance economic productivity using inputs and embrace technologies in 104 countries for a thirty-six-year dataset. This study found that environmental efficiency improved approximately 1.3 percent globally due to energy pricing, restructuring industrial setup, or globalization.…”
Section: The Review Of Literaturementioning
confidence: 99%
“…Renewable energy is the key to limiting greenhouse gas emissions and limiting the increase in global temperature by 2 • [156]. The continents were also investigated: Asia was studied in [157][158][159], and the African continent in [160]. The most localized studies have a concentration on research focused on China [161][162][163].…”
Section: Discussionmentioning
confidence: 99%